Food and Black livingness in the South Carolina Midlands - Ross, Reagan A., author; Chennault, Carrie, advisor; Du, Andrew, committee member; Attai, Nikoli, committee member (Colorado State University. Libraries, 2024)
This thesis explores how food, food spaces, and food sharing practices play a role in the lives of Black women in Newberry County, South Carolina. In particular, it explores how power relations take shape at the intersection of southern foodways and Black geographies via the everyday and intimate practices in the lives of Black women and their communities. Using ethnographic methods informed by Black feminist and community-engaged methodologies, I collaborated with community members in Newberry County over the summer and winter of 2023 to document and examine how plantation histories have impacted intergenerational knowledge sharing and feelings of personal and community empowerment, and how community members rely on themselves and one another, particularly through food sharing practices, to defy ongoing systematic oppressions. Using a critical and Black feminist approach, the first empirical chapter explores the connection between creativity and care work in food sharing practices when examined as an expression of aesthetic labor. Looking to Black geographies and Black feminist scholarship, the second empirical chapter explores how community members employ self-intimacy and spirituality as intimate strategies of resistance and liberatory world-build in and through food spaces. The motivation for this thesis came first and foremost from the desires of community members to document and preserve their knowledges, particularly those related to food and its impact on their lives and communities. This research is also intended to contribute to geographic and critical food literature by calling into question the ways in which much of southern foodways and southern foodways scholarship have sought to erase Black geographies and, even more importantly, by centering Black life, livingness, and sense of place in food spaces.
Keywords: critical food studies; southern foodways; critical geographies; Black feminisms